The technology effect, green consumption and age in propensity to collaborative consumption - Paro, Carlos Eduardo; Ribeiro da Silva, Hermes Moretti [UNESP]; Spers, Eduardo Eugênio; Jugend, Daniel [UNESP]; Hamza, Kavita Miadaira (Elsevier, 2021)
Although several studies point to the emerging importance of technology in consumer habits, limited studies have quantitatively shown how these variables influence consumer intention. Given this gap, this study offers an analytical model based on technology readiness, collaborative consumption intention and green consumption values, using age groups as a moderating variable. Through covariance-based structural equation modeling (CB-SEM) and a sample of 374 respondents (238 younger and 136 older subjects), it was observed that technology readiness positively influences collaborative consumption intention, with green consumption values as a precursor. This relationship is stronger for older people, who generally have a lower perception of the control of technology than younger people. Public strategies and policies to encourage collaborative consumption must, therefore, take into account consumer values and age. Future studies could validate the results presented in this study, and include other demographic and behavioral dimensions.
Keywords: Age groups; Collaborative consumption; Covariance-based structural equation modeling (CB-SEM); Green consumption values; Technology readiness